2013
DOI: 10.1159/000346687
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Clinical and Cost Effectiveness of Growth Hormone Replacement Therapy before and during Puberty: Should We Increase the Dose?

Abstract: Aim: To investigate the influence of growth hormone (GH) on linear growth before and during puberty in children with GH deficiency. Methods: We analysed the relationship between pubertal growth and GH dose in a large dataset of children (n = 236) with GH deficiency using multiple linear regression and multilevel modelling with repeated measures analysis. Additionally, we examined the cost benefit of increasing doses of GH during puberty. Results: Multilevel modelling revealed a highly significant role for GH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
4
0
3
Order By: Relevance
“…In summary, we confirm results from the only previous randomized study using high GH doses [24]. The widespread assumption, based on observational nonrandomized studies [27,30], that pubertal height gain cannot be improved by increasing GH dose during puberty, is not supported by the present randomized study in our large cohort.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In summary, we confirm results from the only previous randomized study using high GH doses [24]. The widespread assumption, based on observational nonrandomized studies [27,30], that pubertal height gain cannot be improved by increasing GH dose during puberty, is not supported by the present randomized study in our large cohort.…”
Section: Discussionsupporting
confidence: 70%
“…Another approach, a stepwise increase in GH dose during puberty from 30 to 60 µg/kg/day, was evaluated in a single-center US study [25]: AH was greater (by 4-5 cm) compared with matched patients from the observational data of the National Collaborative Growth Study - NCGS (Genentech). Earlier studies that have generally used lower dose ranges, for example those using observational data from the Kabi (Pfizer) International Growth Study - KIGS, have found the influence of GH dose to be less pronounced [26,27]. The effects of dose on growth were also less pronounced in the small but randomized studies by Coelho et al [28] and Sas et al [29], in which patients with IGHD and MPHD were randomized to either 25 or 50 µg/kg/day [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that a daily dose of 0.025 to 0.035 mg/kg/d is sufficient to increase growth velocity to more than 10 cm/y in children with severe GHD and the adult height in treated patients ranges from Ϫ1.5 to Ϫ0.8 SDS depending on the study (265)(266)(267)(268). Girls (269) and adolescents (270,271) may require higher doses; however, there is no consistent evidence that an increase in the dose of rhGH peripubertally has a beneficial effect with respect to adult height (272)(273)(274).…”
Section: Box 2 Biochemical Diagnosis Of Ghd In Childhoodmentioning
confidence: 99%
“…This economic analysis is in line with the costs that the Italian Health System estimates for GH treatment and with NICE guidelines, which suggest that GH costs approximately EUR 7.355 per cm final height on average for idiopathic GHD (3). A previous study showed that higher absolute doses of GH produce little benefit in height gain after pubertal onset but rather simply raise the treatment costs (22). In this context, our results might offer a good alternative: it might be beneficial to retest all GHD patients at mid-puberty and then evaluate in a subsequent study whether only patients with persistent GHD benefit from higher doses in order to improve their final stature.…”
Section: Discussionmentioning
confidence: 80%